OPTIMIZATION AND CHARACTERIZATION OF ELECTRON BEAM RESIST USING ATOMIC FORCE MICROSCOPY - Sutikno, - (Jurnal Pendidikan Fisika Indonesia, 2009)
Resis negatif ma-N 2403 dan 495 K PMMA memiliki resolusi yang baik untuk aplikasi litografi berkas elektron (EBL). Ketebalanresist optimal memainkan peran penting dalam paparan berkas elektron. Oleh karena itu, dalam penelitian ini, ketebalan darikedua resist yang dioptimalkan menggunakan spincoater dalam jangkauan laju spin 1000-6000 rpm. Semakin laju spin meningkat,ketebalan resist menurun juga. Morfologi permukaan resist dikarakterisasi dengan mikroskop gaya atom. Butir butir resist nampakpanjang. Dalam analisis AFM, permukaan profil resist negatif ma-N 2403 dan 495 K PMMA nampak seperti kerucut.ÃÂ Negative resist ma-N 2403 and 495 K PMMA have good resolution for electron beam lithography (EBL) application. The optimumresist thickness plays significant role in e-beam exposure. Therefore, in this research, thicknesses of both resists were optimizedusing spincoater within spin speeds of 1000-6000 rpm. As spin speed increased, resist thickness decreased as well. Morphology ofresist surfaces were characterized using atomic force microscopy (AFM). Grains of resist show long grains. In AFM analyses,surface profiles of negative resist ma-N 2403 and 495 K PMMA show cone peaks.Keywords: e-beam resist; spincoater; e-beam lithography